Spectrum Management Reform and the Notion of the 'Spectrum Commons' - Hatfield, Dale N. (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2003)
Spectrum management is an extremely important part of telecommunications policy and regulation. The allocation of spectrum for particular uses, and development of specific technical and service rules governing those allocations, are crucial determinants of telecommunications industry structure and performance. Not only does the management of the resource have an enormous impact on a nation’s economic and social well-being, it is also of critical importance to the safety of life and property, and to national defense. Fast-growing demand, coupled with rapid technological change, have put increased pressure on the traditional, centralised, often bureaucratic, “command-and-control” methods of managing the resource. One alternative to the traditional, centralised method is moving spectrum management in the direction of a marketoriented solution, wherein property-like rights in the resource are traded on a decentralised basis, more like other resources. Another method for reducing the rigidities in the current system is for policy-makers to move spectrum management in the direction of a “spectrum commons” solution. Under this alternative, anyone can gain access to a particular block of spectrum or set of channels, subject only to certain basic rules. Recently, there has been increased interest in the spectrum commons approach, because of the success of unlicensed spectrum in providing consumer benefits and increased opportunities for entrepreneurial activity. This paper explores the spectrum commons approach and concludes that, even in the face of significant challenges, the potential benefits are significant enough to warrant serious consideration by telecommunications policy-makers in their role as spectrum managers. This conclusion applies not only to developed countries but also to developing countries, where the more decentralised, less bureaucratic approach could empower individuals and communities to expand networks, applications and services on their own initiative.